Difficulty of Severe Post-liposuction Infragluteal Deformity Correction With Autologous Fat Transplantation: A Case Report - Yang, Mingzi; Gu, Yunpeng; Sun, Jingjing; Lv, Qianwen; Qi, Yue; Jin, Ji; Liu, Zhenjun; Ma, Guie (Frontiers in Surgery, 2022)
Overaggressive liposuction of the infragluteal region can lead to iatrogenic infragluteal fold deformity and result in esthetic defects in the gluteal contour. We report a case of using autologous fat transplantation to correct severe post-liposuction infragluteal fold deformity. In the process of reconstruction, the patient experienced fat graft overabsorption, fat graft translocation and gluteal ptosis aggravation. Despite multiple operations, the effect of fat transplantation was limited. In conclusion, severe post-liposuction infragluteal deformity is very difficult to correct. The infragluteal region should be preserved during liposuction to avoid deformity.